Microbiology and Outcomes of Institutionalized Patients With Stroke-Associated Pneumonia: An Observational Cohort Study - Jie Zhao (Frontiers Media S.A., 2021)
Background: The attributable mortality and microbial etiology of stroke-associated pneumonia (SAP) vary among different studies and were inconsistent.Purpose: To determine the microbiology and outcomes of SAP in the lower respiratory tract (LRT) for patients with invasive mechanical ventilation (MV).Methods: In this observational study, included patients were divided into SAP and non-SAP based on a comprehensive analysis of symptom, imaging, and laboratory results. Baseline characteristics, clinical characteristics, microbiology, and outcomes were recorded and evaluated.Results: Of 200 patients, 42.5% developed SAP after the onset of stroke, and they had a lower proportion of non-smokers (p = 0.002), lower GCS score (p < 0.001), higher serum CRP (p < 0.001) at ICU admission, and a higher proportion of males (p < 0.001) and hypertension (p = 0.039) than patients with non-SAP. Gram-negative aerobic bacilli were the predominant organisms isolated (78.8%), followed by Gram-positive aerobic cocci (29.4%). The main pathogens included K. pneumoniae, S. aureus, H. influenzae, A. baumannii, P. aeruginosa, E. aerogenes, Serratia marcescens, and Burkholderia cepacia. SAP prolonged length of MV (p < 0.001), duration of ICU stay (p < 0.001) and hospital stay (p = 0.027), shortened MV-free days by 28 (p < 0.001), and caused elevated vasopressor application (p = 0.001) and 60-day mortality (p = 0.001). Logistic regression analysis suggested that patients with coma (p < 0.001) have a higher risk of developing SAP.Conclusion: The microbiology of SAP is similar to early phase of HAP and VAP. SAP prolongs the duration of MV and length of ICU and hospital stays, but also markedly increases 60-day mortality.